1970
DOI: 10.1136/gut.11.10.826
|View full text |Cite
|
Sign up to set email alerts
|

Dose response relationships of insulin hypoglycaemia and gastric acid in man

Abstract: SUMMARY Fourteen studies of gastric acid secretion in a basal hour and in the two hours after a single intravenous injection of soluble insulin (0.01 to 0.40 units/kg) were performed in a healthy man. The peak acid output after insulin (measured as the two consecutive 15-minute samples giving the highest acid output) was significantly correlated with the lowest concentration of blood glucose, the fall in blood glucose, the rate of fall of blood glucose, and the maximum fall of blood glucose in any 15 minutes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
15
0
3

Year Published

1973
1973
1977
1977

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 44 publications
4
15
0
3
Order By: Relevance
“…The secretion of acid in response to insulin presented here agrees with those of previous dose-response studies in healthy man [2,4], These workers found the secretion of acid in response to insulin was related to both the dose of insulin and the degree of hypoglycaemia. This relationship has since been reported in man when the insulin was given by continuous intravenous in fusion [3], In the two healthy men previously reported very low levels of blood glucose, which did not necessarily occur after the largest dose of insulin, were associated with an inhibition of acid secretion.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The secretion of acid in response to insulin presented here agrees with those of previous dose-response studies in healthy man [2,4], These workers found the secretion of acid in response to insulin was related to both the dose of insulin and the degree of hypoglycaemia. This relationship has since been reported in man when the insulin was given by continuous intravenous in fusion [3], In the two healthy men previously reported very low levels of blood glucose, which did not necessarily occur after the largest dose of insulin, were associated with an inhibition of acid secretion.…”
Section: Discussionsupporting
confidence: 82%
“…The variables of gastric acid and blood glucose were expressed as described by Baron [2]. Variables of peptic activity were expressed as follows: basal pepsin output (BPO) was the sum of the peptic activity in the four samples expressed as U x I03/Ii.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These include the insulin test (Hollander, 1948), the ratio of peak acid outputs after insulin and pentagastrin (Baron, 1969) and the ratio of the insulin to histamine acid output (Hunt, 1950). Each has certain drawbacks and occasionally fails owing to difficulties in interpretation and the problem of sample collection in the presence of a drainage procedure.…”
mentioning
confidence: 99%